2020
DOI: 10.1063/1.5125433
|View full text |Cite
|
Sign up to set email alerts
|

Review of the development of copper oxides with titanium dioxide thin-film solar cells

Abstract: Copper oxide-titanium dioxide (TiO 2) p–n junctions are promising materials for photovoltaic devices and may reduce production costs due to their low cost and inexpensive production methods compared with silicon solar cells. The present review compares solar cells made with copper oxides combined with TiO 2–TiO 2/Cu 2O and TiO 2/CuO heterojunctions, and “cascade heterojunction systems.” First, we describe the main properties of titanium (iv) dioxide (TiO 2), cuprous oxide (Cu 2O), and cupric oxide (CuO), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 167 publications
1
28
0
1
Order By: Relevance
“…It also helps to increase the efficiency of the solar cell. A promising materials used as an HT-EBL layer in CdTe solar cells are cuprous oxide (Cu2O) and cupric oxide (CuO), which have a large band gap in the range of 2.1 -2.61 eV and ~ 1.51 eV and p-type conductivity [38,39]. CuO and Cu2O are characterized as non-toxic materials that are available, inexpensive and have a high absorption coefficient in the visible range [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also helps to increase the efficiency of the solar cell. A promising materials used as an HT-EBL layer in CdTe solar cells are cuprous oxide (Cu2O) and cupric oxide (CuO), which have a large band gap in the range of 2.1 -2.61 eV and ~ 1.51 eV and p-type conductivity [38,39]. CuO and Cu2O are characterized as non-toxic materials that are available, inexpensive and have a high absorption coefficient in the visible range [40].…”
Section: Resultsmentioning
confidence: 99%
“…In this study a simulation of the back contact layer of thin-film CdTe solar cells using CuO and Cu2O materials were conducted. In particular, it was found that the material of the back contact affects the efficiency of the final cell, , but the obtained data for Cu2O as a back contact material have shown that adding of this layer did not significantly increase the efficiency of the final cell due to the energy difference of the band gap at the transition CdTe/Cu2O [39]. Accordingly, it was decided to add a layer of CuO.…”
Section: Resultsmentioning
confidence: 99%
“…To offer an efficient ohmic contact assisting carrier recombination, TCOs such as ITO, IZO, and ZTO should feature a conduction band positioned at the valence band of p-type Si with a high work function (or vice versa for the opposite polarity Figure 10. Band alignment diagram of various materials including metal, [215,216] metal compounds, [217][218][219] Si-based passivation layer, [220][221][222][223][224] metal oxides, [138,185,218,[224][225][226][227][228][229] and organic semiconductors and perovskite relative to vacuum level. [230] Fermi level positions are shown as dashed lines.…”
Section: Materials Design For Interconnectionsmentioning
confidence: 99%
“…Band alignment diagram of various materials including metal, [ 215,216 ] metal compounds, [ 217–219 ] Si‐based passivation layer, [ 220–224 ] metal oxides, [ 138,185,218,224–229 ] and organic semiconductors and perovskite relative to vacuum level. [ 230 ] Fermi level positions are shown as dashed lines.…”
Section: Interconnection Structure and Materialsmentioning
confidence: 99%
“…The last improvements concern the optimization of the band alignment of the structure by carefully selecting the buffer layer material. In fact, one limitation of the use of Cu 2 O as the absorber layer is its low electron affinity x = 2.1 eV which creates a conduction band offset with the buffer layer which is typically made of zinc oxide (x = 4.4 eV) [8] or titanium oxide (x = 4.1 eV) [9]. Previous simulations show that the reduction of the electron affinity of the buffer layer to 3.2 eV enhances the efficiency of the device [10].…”
mentioning
confidence: 99%